The Definitive Guide to Spring Web Flow - Vervaet, Erwin (Springer, 2017)
Spring Web Flow is an exciting open-source framework for developing Java web applications. The framework improves productivity by addressing three major pain–points facing web application developers: user interface navigation control, state management, and modularity.